2009
DOI: 10.1007/s12016-009-8144-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Pregnancy Outcome in Antiphospholipid Syndrome: A Review

Abstract: In pregnant women, antiphospholipid syndrome (APS) is associated with an increased risk of preeclampsia, fetal intrauterine growth restriction, and other complications related to uteroplacental insufficiency. In the last two decades, several studies were performed to identify the predictive role of some parameters in relation to obstetric outcome in APS patients. Among these, the uterine velocimetry Doppler is the most studied. It provides a non-invasive method for the study of uteroplacental blood flow, being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…IVIG intravenous immunoglobulins, HCQ hydroxychloroquine virus tests) was an independent predictor of lower neonatal birth weight [46]. However, a subsequent study failed to report any association between hypocomplementemia and obstetric complications [47].…”
Section: Authors (Reference) Year Clinical Reports Treatment Protocolmentioning
confidence: 96%
“…IVIG intravenous immunoglobulins, HCQ hydroxychloroquine virus tests) was an independent predictor of lower neonatal birth weight [46]. However, a subsequent study failed to report any association between hypocomplementemia and obstetric complications [47].…”
Section: Authors (Reference) Year Clinical Reports Treatment Protocolmentioning
confidence: 96%
“…Outcome studies have shown that the rate of fetal loss is up to 18% during APS pregnancies compared with a rate of early fetal loss of 1% and a rate of second and third trimester fetal demise of 5% in the general population (3;8;9). The reported frequency of IUGR in APS pregnancies ranges from 13 to 33% (8;10;11), and aPL are detected in 25% of women whose infants suffer from IUGR (3). Premature delivery occurs in 16 to 50% of APS pregnancies despite maternal therapy, with an average gestational age at birth of 31 weeks in one study (8;11;12).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional treatment based on low molecular weight heparin (LMWH) and low-dose aspirin (LDA) is associated with a rate of live birth of almost 80% [1][2][3]. Despite these encouraging results, some APS patients remain unable to give birth to healthy neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been performed in order to identify risk factors predictive of complications despite the conventional treatment [3,4].…”
Section: Introductionmentioning
confidence: 99%